'Community control' in CBPR: Challenges experienced and questions raised from the Trans PULSE project. Issue 4 (December 2013) - Travers, Robb; Pyne, Jake; Bauer, Greta; Munro, Lauren; Giambrone, Brody; Hammond, Rebecca; Scanlon, Kyle
Newer forms of community-based participatory research (CBPR) prioritize community control over community engagement, and articles that outline some of the challenges inherent in this approach to CBPR are imperative in terms of advancing knowledge and practice. This article outlines the community control strategy utilized by Trans PULSE, an Ontario-wide research initiative devoted to understanding the ways in which social exclusion, cisnormativity (the belief that transgender (trans) identities or bodies are less authentic or 'normal'), and transphobia shape the provision of services and affect health outcomes for trans people in Ontario, Canada. While we have been successful in building and supporting a solid model of community control in research, challenges have emerged related to: power differentials between community and academic partners, unintentional disempowerment of community members through the research process, the impact of community-level trauma on team dynamics, and differing visions about the importance and place of anti-racism work. Challenges are detailed as 'lessons learned' and a series of key questions for CBPR teams to consider are offered.